Coping strategies in caregivers of patients with diabetes mellitus type-1 - Noshaba Noor,; Mohsina Noor Ibrahim,; Fawad Suleman Roonjho,; Karishma Rahak,; Usman Tauseef, (Journal of the Pakistan Medical Association, 2025)
Objective: To determine coping strategies in caregivers of children with type-1 diabetes mellitus. Method: This cross-sectional study was conducted at the Outpatient Department of Paediatric Endocrinology, National Institute of Child Health, Karachi, from September 2022 to October 2023, and comprised caregivers aged up to 60 years of children aged 1-14 years who were known cases of type 1 diabetes mellitus. Coping strategy scoring and interpretation was done using the shorter 28-item version of the Coping Orientation to Problems Experienced Inventory. Data was analysed using SPSS 26. Results: Of the 227 caregivers with mean age 39.93±7.13 years, 106(46.7%) were mothers. Among the children with mean age 12.79±4.27 years, 127(55.9%) were girls. The mean duration of care was 5.71±4.05 years. Coping strategies were found present among 99(43.6%) caregivers. The age of the caregivers with coping strategies was significantly higher compared to those without coping strategies (p<0.001). Among the caregivers with coping strategies, there were significantly more Urdu-speaking individuals than of any other language (p=0.025). Parents whose children were literate were more likely to have coping strategies (p=0.022). Conclusion: Recognizing that age of the caregivers and language may influence coping strategies, healthcare providers should consider tailoring support and interventions to the specific needs of caregivers in different age groups and linguistic communities. The association between a child's education level and parental coping strategies highlights the importance of involving children in their care management. Key Words: Brief-COPE, Caregivers, Parents, Type-1 diabetes mellitus, Urdu.